AB1313 NMR SPECTROSCOPY REVEALS ALTERATIONS OF URINARY ACETATE AND CITRATE LEVELS FOLLOWING CYCLOPHOSPHAMIDE THERAPY IN PATIENTS WITH LUPUS NEPHRITIS. (June 2019) - Ganguly, Sujata; Kumar, Umesh; Gupta, Nikhil; Guleria, Anupam; Majumdar, Sanjukta; Phatak, Sanat; Chaurasia, Smriti; Aggarwal, Amita; Kumar, Dinesh; Misra, Ramnath
Abstract : Background: Metabolomics, the study of global alterations in small metabolites is a useful tool to look for novel biomarkers. Recently, we reported a reprogramming of the serum metabolomic profile on nuclear magnetic resonance(NMR) spectroscopy following treatment in Lupus Nephritis (LN) [1] . Objectives: We explored urinary parameters using NMR Spectroscopy in patients with biopsy proven proliferative lupus nephritis. Change in parameters after 6 months Cyclophosphamide induction treatment and its correlation with disease activity was assessed. Methods: Urine obtained from Lupus Nephritis (n=18, F=16, M=2) at diagnosis and following induction therapy with cyclophosphamide, and healthy controls (n=18, median age 35, all females) were stored at -80 °C. Metabolomic profiling was done using high resolution 800 MHz 1D 1H NMR spectroscopy. Urinary ratio of metabolites was calculated- (Metabolitex1000)/Creatinine. Disease activity was measured using SLEDAI. Metabolomic profiles were compared between groups and correlated with clinical parameters using SPSS. Results: Urinary metabolomic fingerprint of LN patients differed from healthy controls by having significantly raised urinary acetate/creatinine(LN=41.84±100.6, HC=12.36±9.40, p=<0.002) and reduced urinary citrate/creatinine.(LN=34.22±54.8, HC=114.5±70.09, p=<0.0001). Urinary citrate (88.68±98.33) increased after 6 months of Cyclophosphamide, while urinary acetate showed a trend towards decrease(14.77±9.98). AUC for urinary citrate/creatinine and acetate/creatinine were 0.9136 and 0.8086. The urinary acetate levels correlated with SLEDAI (r=0.337, p=0.048). Urinary citrate levels correlated with C3 (r=0.362, p=0.03) and negatively correlated with uPCR (r=0.346, p=0.039). Conclusion: The decreased urinary citrate mirrors the finding seen in serum of the patients done earlier which reflects dampened aerobic glycolysis and oxidative phosphorylation.(1) Raised urinary acetate levels possibly reflects proximal renal tubular injury leading to increased urinary excretion(2). Change in levels with treatment show that urinary metabolomics parameters are potential noninvasive biomarkers for diagnosis and monitoring treatment response in LN References: [1] Guleria A, et al. NMR based serum metabolomics reveals reprogramming of lipid dysregulation following Cyclophosphamide based induction therapy in lupus nephritis. J Proteome Res. 2018, 17 (7), 2440–2448. [2] Gartland KP, Bonner FW, Nicholson JK. Investigations into the biochemical effects of region-specific nephrotoxins. Molecular Pharmacology. 1989 Feb 1;35(2):242-50. Disclosure of Interests: None declared